Pemberdayaan Masyarakat melalui Menejemen Bank Sampah Berbasis Website - Supriyanti, Yuni Indah; Imron Rosyadi; Hania Sumarni; Hevi Novriani; Kevin Ardiansa (Program Studi Administrasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Bengkulu, 2024)
Kemumu Village was originally in the form of a village named Sido Mulya from the Dutch Colonization Transmigration Program in 1935 which came from Banyumas, and Kebumen, Central Java. In 2023 Kemumu won 2nd place in the Competition and in 2024 won first place at the Provincial level. With this achievement, of course, the Village assisted by related parties such as TP-PKK and POKDARWIS must strive to create tourist locations to be cleaner, more beautiful, neat and comfortable to visit. However, this effort is not balanced by the awareness of visitors in throwing garbage. Visitors still throw garbage carelessly at interesting tourist spots. This makes tourist locations unbeautiful. Kemumu as a biowealth-based ecotourism destination and agrotourism with tourist spots in swampy areas are filled with a lot of garbage. This causes pollution, the flow of water is obstructed. The 2018 DRTPM PKM program has succeeded in forming a waste artisan center and has succeeded in improving community skills in utilizing plastic waste into goods of economic value. However, along with the increase in knowledge, understanding and behavior of the community in utilizing plastic waste, it has an impact on the lack of plastic waste supply needed by craftsmen. Meanwhile, the people of Kemumu have the potential to produce plastic waste. Through PMP 2024, it tries to provide solutions on how to manage plastic waste in order to create a sustainable tourism village, and increase awareness in waste management, increase knowledge, waste management skills so that it can meet the needs of waste artisans and community income with socialization, training, technology application, mentoring, and evaluation methods. The results of PMP 2024 have been able to increase the knowledge, understanding and skills of partners in managing plastic waste so that waste artisans no longer have difficulty in obtaining raw materials. The Arga Tirta Waste Bank has been formed which is located in the Palak Siring Kemumu Field